Rancang Bangun Sistem Kontrol dan Web Kamera pada Smart Autopilot Unmanned Ship Berbasis Web Real Time Communications (Web-RTC) - Moh. A. Khunaifi; Dwi S.A. Pambudi; Afif Z. Arfianto (SAINTARA, 2022)
The Design of Control Systems and Web Cameras on Smart Autopilot Unmanned Ship (SAUS) Based on Web Real Time Communications (Web-RTC) is a research conducted to develop from the results of research that has been studied by previous researchers, as well as develop according to the suggestions mentioned by previous researchers, such as displaying map data and live cameras on the web interface and being able to store ship movement data displayed on maps. And it can also be used as a monitor for the history of the trips that have been made by the ship. In conducting this research, researchers used the Web Real Time Communication (Web-RTC) method as live camea delivery and MQTT as data transmission to control the movement of the ship which was driven using an outboard motor with the help of an actuator in the form of a hydraulic engine to turn the ship. From the results and explanations that have been described by the researcher, it is concluded that to make this research a web server is needed as a place to put data in the form of MQTT Broker data, GPS delivery data and data to display the web interface. Meanwhile, to transmit realtime video from a webcam connected to a raspberry, it uses Web-RTC as a connecting medium or bridges the transmission of realtime video data. As a recommendation for further research, you can add video storage of each ship's journey, so that you can monitor all the ship's journeys and can be used as an evaluation for the next ship's journey.